INFLUENCE OF FINANCIAL ADMINISTRATION AND ACCOUNTING INFORMATION SYSTEMS ON THE QUALITY OF REPORTS REGIONAL FINANCE - Indrawaty Nurdin; Muhammad Aqsa; Rismawati; Imam Pribadi; Duriani, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The quality of financial reports is a vital element in public financial management, especially in the government sector. This research aims to examine the influence of Financial Administration and Accounting Information Systems on the quality of financial reports in Work Units in East Luwu Regency. The research methodology was carried out using quantitative methods by carrying out the Patrial Squere Test, using research samples with primary data sources, namely questionare. Research Location at East Luwu Regency Regional Work Unit. The research results show that financial administration has a significant influence on the quality of financial reports. Accounting Information Systems (AIS) have a positive but not significant influence on the quality of financial reports. The conclusion that can be made is that effective financial administration plays an important role in improving the quality of financial reports, while the accounting information system, although positive, requires further optimization to have a significant impact. Local governments and work units in East Luwu Regency need to adopt strategic steps to strengthen these two aspects in their efforts to increase financial transparency and accountability in the future.